2013
DOI: 10.2478/s11535-013-0191-4
|View full text |Cite
|
Sign up to set email alerts
|

Do Ca2+-chelating polysaccharides reduce calcium ion release from gypsum-based biomaterials?

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(44 reference statements)
1
3
0
Order By: Relevance
“…Following this hypothesis, such a deposition and pores clogging could probably reduce the surface area of HAp granules and slow down the rate of further uptake of Ca 2+ and PO 4 – ions. Release of Mg 2+ ions, parallel with the uptake of Ca 2+ and PO 4 – ions, is in agreement with our earlier results where such a specific Mg 2+ /Ca 2+ uptake/release equilibrium was observed for HAp/gypsum composite . One should remember, however, that the phenomenon of ions absorption‐desorption from the composite was observed for five days only.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Following this hypothesis, such a deposition and pores clogging could probably reduce the surface area of HAp granules and slow down the rate of further uptake of Ca 2+ and PO 4 – ions. Release of Mg 2+ ions, parallel with the uptake of Ca 2+ and PO 4 – ions, is in agreement with our earlier results where such a specific Mg 2+ /Ca 2+ uptake/release equilibrium was observed for HAp/gypsum composite . One should remember, however, that the phenomenon of ions absorption‐desorption from the composite was observed for five days only.…”
Section: Discussionsupporting
confidence: 93%
“…Perhaps traces of apatite were formed on the composite surface but they were deposited within micropores of HAp granules (approximately 100 nm in size, as reported elsewhere 14 ) and this could explain the decreasing rate of Ca 21 -ions, is in agreement with our earlier results where such a specific Mg 21 /Ca 21 uptake/release equilibrium was observed for HAp/gypsum composite. 30 One should remember, however, that the phenomenon of ions absorption-desorption from the composite was observed for five days only.…”
Section: Discussionmentioning
confidence: 99%
“…4-fold) the growth rate of S. aureus (for C + CSD in comparison with C biomaterial), which can be explained by the stimulatory effect of calcium ions released by CSD. Calcium ions have been reported to affect the growth and metabolism of all organisms, including different bacteria, in a concentration-dependent manner [34][35][36]. This effect was not observed for E. coli (the viability of bacteria for C and C + CSD samples was similar).…”
Section: Antibacterial Activitymentioning
confidence: 97%
“…It has already been shown that the application of calciumchelating polysaccharides (alginates or rhizobial exopolysaccharides) as a supplement to gypsum-based composite does not provide a sufficient, long-term efficacy in the removal of the excess of gypsumreleased Ca 2+ ions [13]. However, another concept may be tested for this purpose: the use of calcium ion-adsorbing ceramics.…”
Section: Introductionmentioning
confidence: 99%